Analysis and Visualisation of Research Trends in Nano Material: A General Review - Kumar, Ranvijay (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technically, the material possessing a minimum, one external dimension measuring 1-100nm is called Nanomaterial, and cannot be seen by the naked eye. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Nanomaterial”[1], [2]. All published articles related to “Nanomaterial” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps.This article had set the objective to consolidate the scientific literature regarding the “Nanomaterial”and also to find out the trends related to the same.The most active journals in this research domain were Construction and Building Materials and Composites Science and Technology. The most active countries were China and the United States of America. The leading organizations engaged in the research regarding Nanomaterial was the Chinese Academy of Sciences, the North Eastern University of China, and the Ministry of Education of China.The most active authors who had made valuable contributions related to Nanomaterial were Wang Y. and Yang H.